2022
DOI: 10.3389/fpsyt.2022.993356
|View full text |Cite
|
Sign up to set email alerts
|

Shared and distinct functional connectivity of hippocampal subregions in schizophrenia, bipolar disorder, and major depressive disorder

Abstract: Schizophrenia (SZ), bipolar disorder (BD), and major depressive disorder (MDD) share etiological and pathophysiological characteristics. Although neuroimaging studies have reported hippocampal alterations in SZ, BD, and MDD, little is known about how different hippocampal subregions are affected in these conditions because such subregions, namely, the cornu ammonis (CA), dentate gyrus (DG), and subiculum (SUB), have different structural foundations and perform different functions. Here, we hypothesize that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The results showed that the temporal lobe volume and CBF values were lower in ADHD children than in healthy children, suggesting that the temporal lobe is less developed in ADHD children; the temporal lobe is mainly responsible for processing auditory information, while the temporal lobe also has some relationship with memory and emotion ( 35 ). Generally, the temporal lobe is supplied by the middle cerebral artery, which is part of the blood supply of the cerebral anterior circulation ( 36 ). Patients with temporal lobe lesions may experience memory loss or emotional disorders, such as mental excitement or depression and emotional disturbance, and in severe cases, hallucinations or delusions may occur, and some patients may also present with temporal lobe epilepsy ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the temporal lobe volume and CBF values were lower in ADHD children than in healthy children, suggesting that the temporal lobe is less developed in ADHD children; the temporal lobe is mainly responsible for processing auditory information, while the temporal lobe also has some relationship with memory and emotion ( 35 ). Generally, the temporal lobe is supplied by the middle cerebral artery, which is part of the blood supply of the cerebral anterior circulation ( 36 ). Patients with temporal lobe lesions may experience memory loss or emotional disorders, such as mental excitement or depression and emotional disturbance, and in severe cases, hallucinations or delusions may occur, and some patients may also present with temporal lobe epilepsy ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al [ 32 ] found increased FC between the bilateral hippocampus (mainly CA regions) and between the hippocampal CA regions and right insula in patients with MDD. Song et al [ 33 ] revealed decreased FC between the right hippocampal Subc and right middle frontal gyrus in MDD patients with anti-depressant treatment. Wang et al [ 34 ] demonstrated greater changes in the FC between the left hippocampal CA and bilateral posterior cingulate cortex (PCC) in remitted late-onset depression.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging has been widely employed to investigate the mechanisms that contribute to brain abnormalities in mental disorders [5]. Pathophysiological problems in brain activity have been frequently observed 79 utilizing neuroimaging methods in SZ patients and BD patients with abnormal functional connections may lead to [6,7].…”
Section: Introductionmentioning
confidence: 99%